Application of Project Based Learning Insect Characteristics Around Lake Tondano in Entomology Course - Ferny Margo Tumbel; Yermia Semuel Mokosuli; Meike Paat (Jurnal Biologi Tropis, 2022)
The online learning policy was implemented during the COVID-19 pandemic in various countries around the world. Problems arise in learning biology that requires laboratory experiment activities. This research provides an innovation in entomology learning with a project-based learning method using insect biodiversity in the local ecosystem, namely Lake Tondano. This study aims to determine the ability of science process skills and student responses using the project-based learning method. Project-based learning is one of the methods established for the independent learning process to learn the independent curriculum. The research was conducted with an exploratory, descriptive research method. Science process skills and student project products are measured using a rubric. Student learning outcomes are measured using quiz questions with the google form application.Meanwhile, student responses were measured using a questionnaire. The study results showed that the science process skills of students who were taught using the Project-based learning method were in the good and very good categories. The resulting project output is a practical guide based on the assessment rubric which is in good and very good grades. Student responses regarding the application of Project based learning in entomology courses are in the agree and strongly agree categories. Student learning outcomes showed an average in the good and very good categories. The application of project-based learning can stimulate the ability of science processes and student learning outcomes in entomology courses. Project-based learning is very appropriate to be applied to fields of science that require a lot of experimental activities. Because it is carried out in small research groups, the project-based learning method is appropriate for learning during the COVID-19 pandemic.